Postpartum depression among Malay women from a rural area in Kedah, North West of Peninsular Malaysia: Prevalence and risk factor - WMWM, Rushidi; MR, Hayati; B, Baizuri; Awang, Amir; Mohamed, Mahmood Nazar (Malaysian Psychiatric Association, 2005)
Background: Community based epidemiological data on postpartum depression in Malaysia is scarce.Aim: To determine the prevalence and risk factors for developing postpartum depression among Malay women from a rural area in Kedah, North West of Peninsular Malaysia.Method: We screened 185 women at 4-12 weeks postpartum attending the selected health centers using the Malay versions of Edinburgh Postnatal Depression Scale (EPDS) and Beck Depression Inventory II (BDI-11). Those scoring ≥ 12 and / or ≥ 9/10 on BDI-11 were interviewed using the Composite International Diagnostic Interview (CIDI) and the 17-items Hamilton Rating Scale for Depression(HDRS-17). All diagnoses were based on the Tenth Edition of the International Classification for Disease: Diagnostic Criteria for Research (ICD-I0: DCR-10). Results: The prevalence of postpartum depression was 21.08%. The condition was found to be significantly linked to polygamous marriages, high number of life events and financial problems over the last one year prior to delivery, and low scores on the Malay version of the MOS Social Support Survey and all its components (overall support index, informational support, affectionate support/ positive social interactions and instrumental support). Conclusions: Postpartum depression is indeed a reality among Malay women in rural areas In Kedah, North West of Peninsular Malaysia. These findings have implications for policies regarding maternal and childcare programs.